Hiperviskositas Pada Penyakit Jantung Bawaan (PJB) Sianotik - Febtusia Puspitasari; Ganesja M Harimurti (Jurnal Kardiologi Indonesia, 2010)
Increased whole blood viscosity in adults with cyanotic congenital heart disease (CCHD) is an unavoidable result of secondary erythropoiesis and it showed a significant bleeding tendency. The most frequently disturbance of hemostasis are thrombocytopenia and defective platelet aggregation. Acute phlebotomy without volume replacement in patients with hypoxic polycythemia may result in vascular collapse, cyanotic spells, cerebral vascular accidents (CVA), or seizures and repeated phlebotomies may also increase the risk of a CVA by causing chronic iron deficiency.